A Narrative Review on Overservicing in Mental Health: Definitions, Risks, and Implications for Recovery - Bhusal, Jeevan (Tribhuvan University Journal, 2026)
Overservicing refers to the provision of mental health services that exceed what is clinically indicated within a shared treatment plan. Such practices may undermine autonomy, reduce treatment accountability, distort power dynamics, and impede recovery. Conversely, underservicing can also produce significant countertherapeutic effects, contributing to unmet needs and poorer outcomes. This article examines overservicing in mental health care, clarifies its conceptual boundaries, and analyses its implications for recovery-oriented practice. A narrative review approach was used, drawing on peer‑reviewed literature and established clinical guidelines to synthesise current evidence on overservicing, related constructs, and their impacts. Conceptual analysis was applied to distinguish overservicing from overdiagnosis, overtreatment, excessive referral, and fraudulent practices. Overservicing contributes to dependency, inflates healthcare costs, and disrupts recovery processes. Evidence highlights the importance of clinician self‑awareness, clear communication, and comprehensive biopsychosocial assessment in preventing unnecessary or excessive interventions. Strengthening health literacy and ensuring adherence to evidence‑based, person‑centred treatment planning are key strategies for reducing both over‑ and underservicing. Overservicing is a significant barrier to recovery‑oriented mental health care. Clinicians, particularly social workers, play a central role in mitigating this risk through thorough assessment, collaborative treatment planning, and consistent application of clinical guidelines. Although overservicing is widely discussed in health economics, it remains underexamined within mental health service delivery. This article offers an operational definition tailored to mental health contexts and proposes practical, evidence‑informed strategies to prevent both overservicing and underservicing.